Challenges Faced by Nurses Working in Emergency Unit of BP Koirala Institute of Health Sciences, Dharan - Bhattarai, Smita (Journal of Biratnagar Nursing Campus, 2023)
Introduction: A challenge is regarded as a very difficult situation with a variety of conditions at a given time. Nurses are the major human resources in health care services of the world and are the backbone of the hospital but still they are facing various challenges. The objective of the study was to assess the challenges faced by nurses working in the emergency unit of BPKIHS. Methods: A descriptive cross-sectional study design was used to conduct the study. Fifty nurses who met the eligibility criteria were selected by total enumerative sampling technique. For data collection, self-prepared semi-structured, self-administered questionnaires were used. Collected data was analyzed by using descriptive and inferential statistical tests. Results: The mean age of the respondents was 25.72. Among the challenges, two-thirds (66.0%) of the respondents have faced physical violence. Majority (84.0%) of the respondents have faced psychological violence at least once. More than half (54.0%) of the respondents have faced more stress. More than half (58.0%) of the respondents have faced more workload, nearly two-thirds of the respondents (60.0%) have more salary and employment benefits. Marital status and education level had a significant association with workload domain (p<0.05). Conclusion: Among the challenges, majority of the respondents had faced psychological violence, more than half of the respondents had faced more workload whereas nearly two-thirds of the respondents had more salary and employment benefits.